2022
DOI: 10.1093/jxb/erac103
|View full text |Cite
|
Sign up to set email alerts
|

Kernel weight contribution to yield genetic gain of maize: a global review and US case studies

Abstract: Over the past century of maize (Zea mays L.) breeding, grain yield progress has been the result of improvements in several other intrinsic physiological and morphological traits. In this study, we describe (i) the contribution of kernel weight (KW) on yield genetic gain across multiple agronomic settings and breeding programs, and (ii) the physiological bases for improvements in KW for US hybrids. A global-scale literature review concludes that rates of KW improvement in US hybrids were comparatively similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
4
6
0
Order By: Relevance
“…This finding is very encouraging for future progress in grain yield increase and highlights the important role of maize breeding programs. The reported genetic gain in this study is similar to those found in longer-season hybrid era studies (66-143 kg ha −1 year −1 ; Castleberry et al, 1984;Chen et al, 2016;DeBruin et al, 2017;Duvick, 1984;Fernández et al, 2022; Haegele et al, 2013;Smith et al, 2014). Assefa et al (2017) analyzed plant density by commercial hybrid experiments across latitudes in North America and reported grain yield genetic gains comparable to those found in our study (Figure 8).…”
Section: Grain Yield and Componentssupporting
confidence: 89%
“…This finding is very encouraging for future progress in grain yield increase and highlights the important role of maize breeding programs. The reported genetic gain in this study is similar to those found in longer-season hybrid era studies (66-143 kg ha −1 year −1 ; Castleberry et al, 1984;Chen et al, 2016;DeBruin et al, 2017;Duvick, 1984;Fernández et al, 2022; Haegele et al, 2013;Smith et al, 2014). Assefa et al (2017) analyzed plant density by commercial hybrid experiments across latitudes in North America and reported grain yield genetic gains comparable to those found in our study (Figure 8).…”
Section: Grain Yield and Componentssupporting
confidence: 89%
“…Lower grain yields of modern hybrids were observed with extremely vertical leaves (>75°), which can be associated with reduced light interception (Duncan, 1971). Leaf angle is one of the many secondary traits that maize breeding has altered over the years (Curin et al., 2020; Duvick et al., 2004; dos Santos et al., 2023; Fernández et al., 2022; Troyer, 1999). While we found no strong association between leaf angle and crop yields, we believe that other traits beyond leaf angle have played a larger role in historical grain yield increases (e.g., radiation use efficiency, Messina et al., 2022; N use efficiency, Mueller et al., 2019; water use efficiency, Reyes et al., 2015; harvest index, Ruiz et al., 2023; staygreen, Duvick et al., 2004; anthesis‐silking interval, dos Santos et al., 2023; grain growth rate and extended grain fill period, Gambin et al., 2023) and that the slowing down of the leaf angle genetic gain is of little concern for future grain yield gains.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in corn and soybean yield was associated with an increase in seeds area −1 (for simplicities sake, "seed" will be used to refer to both the soybean seed and the corn caryopsis) (de Bruin & Pederson, 2009;He et al, 2022;Jin et al, 2010;Echarte et al, 2000;Luque et al, 2006;Russell, 1991;Tollenaar et al, 1992;Voldberg et al, 1997). The contribution of seed size was limited in corn (Barker et al, 2005;de Bruin et al, 2017;Fernandez et al, 2022;He et al, 2022;Russell, 1991;). Chen et al (2016), however, reported a significant contribution when the increase in yield was associated with a longer seed filling period.…”
Section: Crop Sciencementioning
confidence: 99%